PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT UNTUK MENINGKATKAN HASIL BELAJAR MEMBIAKKAN TANAMAN SECARA VEGETATIF PADA SISWA KELAS X SMK NEGERI 3 TAKALAR - Triana Aprilia Amin; Muhammad Yahya; Muhammad Wiharto Caronge (Universitas Negeri Makassar, 2018)
This research is a classroom action research that aims to improve student learning result of ATPH class (Agribusiness Of Food Crop And Horticulture) X.1 SMK Negeri 3 Takalar by using cooperative learning model of TGT type on vegetative propagation subject. The research procedure includes stages: (a) planning, (b) implementation, (c) observation, and (d) reflection. The data collected is qualitative data and quantitative data. Based on the results of the study, it can be concluded that the application of cooperative learning model type TGT can improve student learning outcomes seen from the data of test results learning. This is evident in the initial test, cycle I and cycle II student learning outcomes continue to increase. In pre test the average value 66.06 with mastery learning 62.5%, the post test cycle I average value 73.12 with mastery learning 75%, the post test cycle II average value 80.83 with mastery of learning 87.5%